Aqui estou, aqui faço o meu lugar: um estudo sobre percepções e manejo do ambiente entre camponeses, na comunidade de Barra do Pacuí, município de Ibiá MG - Santos, Rodrigo Herles dos (2008)
The present research was developed in São Francisco middle region, in the city of Ibiaí, north of Minas gerais, having as locos empírico the peasant community of Barra do Pacuí. The approach was conducted to investigate how, by being included in the rural world, the peasant of this community can realize, feel, represent and act about the environment in whitch they live and work. To reach this objective, I made an methodological base using procedures and instruments for data collection that brought me as close as I could of a qualitative approach, working in the participative observation practical perspective about the residents daily life, their work relations, or better saying, the Barra do Pacuí peasants way of life. Were made, a communitarian census, free interviews and visual appointments of the observed facts, besides a location map confection, drawing, diagrams and croqui of the studied area. In the theoretical point of view, I treated concepts about the environmental question, the relationship environment and space and, the symbolical and economical constitution of the traditional communities. There were also included issues relating to technical and scientific influence in current geographical space configuration and their repercussion in the rural brazilian world, including the north of Minas Gerais. I call attention to the interlocution with João Guimarães, who was used to constitute between people, scenes and scenarios, the space of the sertão and the transformations that the region has been passing by in consequence of the State political actions since the decade of 1970, specially SUDENE s action. Finally I did an community ethnographical analysis, that allowed me characterize their way of life and ways of handling local environment. Detaching, internal geographical aspects and how, on terms of the peasant economical production, was established in the common uses of the territory a policultura system, including fishing activity, to extract the minimos vitais that can guaranty their political, economical and cultural reproduction.